Barry's advanced construction of buildings - Emmitt, Stephen; Barry, R. (Robin); Gorse, Christopher A. (Chichester, U.K. : Wiley-Blackwell, 2010)
'This new edition of Barry's Advanced Construction of Buildings retains the emphasis on larger-scale buildings: primarily residential, commercial and industrial buildings constructed with load bearing frames. A considerable amount of new material has been added but the text remains faithful to Barry's original concept of explaining construction technology through key functional and performance requirements for the main elements common to all buildings. Of particular note in this new edition is the expanded coverage of building and construction sustainability. This is now presented within the main body of the text, rather than as a separate chapter. Material relating to the Building Regulations has been brought fully up to date, and there is a more thorough treatment of demolition. The rest of the text has been updated as required, with particular attention paid to the illustrations. Advanced undergraduate students and those working towards similar NQF level 5 and 6 qualifications in building and construction will find this the ideal book with which to continue their study of the subject.'--Publisher's description.
Introduction -- Scaffolding, facade retention and demolition -- Ground stability, foundations and substructures -- Single-storey frames, shells and lightweight coverings -- Structural steel frames -- Structural concrete frames -- Cladding and curtain wall construction -- Prefabrication and off-site production -- Lifts and escalators -- Fit out and second fix -- Internal environment and services provision.
Includes bibliographical references and index.
Keywords: Building